Case study on indusrtialized building system (IBS) - Satti Osman, Mohamed AbdelGadir (2006)
The construction industry suffers from many problems. The performance of this industry needs to be greatly improved if it so to survive from international competition and increased customer expectations. The building industry which is still very traditional should move towards full industrialization to achieve higher quality, less time and reduce cost. This can be benefited by learning more from manufacturing industry. Industrialised construction methods could be a practical alternative to traditional construction methods for construction projects. Industrialized construction methods are not much used in building projects. In this research three case studies where undertaken. These case studies were companies applying industrializing building systems in their projects. These projects have been conducted in relation with construction and manufacturing process. A number of visits and interviews were held to manufacturing factories of prefabricated components and construction sites and some governmental bodies such as CIDB. This was accomplished by designing a questionnaire and presenting it to a number of people in different positions related to this field. It has been found that manufacturing and prefabrication in building offers a range of potential benefits to those who choose to use them. Quality control and precision can be sustained at a higher level in prefabricated building components due to the controlled factory working conditions and advanced technology available. Other benefits include a reduced number of material deliveries to the job site, resulting in less coordination conflicts among trades. Even though IBS is not new in the Malaysian construction, the usage is still very low compared to conventional methods due to number of problems bordering these methods, and limiting them from expanding. These problems are also studied, and some conclusions and recommendation are given.